2016
DOI: 10.1111/jai.13164
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationship of six deep-sea fish species from the shelf regions of western Bay of Bengal and Andaman waters

Abstract: Summary Length–weight relationships for six deep‐sea fish species inhabiting the shelf regions of the western Bay of Bengal and the waters of Andaman and Nicobar of India are presented. Samples were collected using high‐speed demersal trawl and expo demersal trawl nets at depths of 231–514 m in August and September 2010. The b values in the analyses ranged from 3.05 to 3.31, showing a mean and median value of 3.21 (SE ± 0.039, SD ± 0.097) and 3.2, respectively. Comparisons of b values with earlier estimations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Variations in the growth parameters have been discussed by several authors (Jayaprakash et al, 2006;Sreedhar et al, 2013;Thomas et al, 2003), but most studies did not consider that non-standardized sampling procedures might have partially caused this variation. Previous studies have reported that factors such as maturity, season, depth of capture, area, sex, length class, sample size, gear selectivity and hydrographical differences have significant effects on the LWRs and growth patterns in fishes (Kumar et al, 2016;Mommsen, 1998;Sreedhar et al, 2013;Thomas et al, 2003). Using length-weight data from locally available fish stocks improves the LWR estimations significantly; caution must be exercised to restrict the application to specific length ranges from which the LWR is estimated (Morey et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the growth parameters have been discussed by several authors (Jayaprakash et al, 2006;Sreedhar et al, 2013;Thomas et al, 2003), but most studies did not consider that non-standardized sampling procedures might have partially caused this variation. Previous studies have reported that factors such as maturity, season, depth of capture, area, sex, length class, sample size, gear selectivity and hydrographical differences have significant effects on the LWRs and growth patterns in fishes (Kumar et al, 2016;Mommsen, 1998;Sreedhar et al, 2013;Thomas et al, 2003). Using length-weight data from locally available fish stocks improves the LWR estimations significantly; caution must be exercised to restrict the application to specific length ranges from which the LWR is estimated (Morey et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Length-weight relationships (LWRs) are of great importance in the area of fisheries research as they are used to predict the condition and growth pattern, as well as calculate the biomass from the length, and to convert growth in length to growth in weight (Froese, 2006;Froese, Thorson, & Reyes, 2014;Froese, Tsiklirans, & Stergiou, 2011;Le Cren, 1951;Sandoval-Huerta, Madrigal-Guridi, Domínguez-Domínguez, Ruiz-Campos, & González-Acosta, 2015). The biology, ecology and life history characteristics of deep-sea fishery resources from the Indian EEZ are scarce and scattered (Deepu, Divya, & Kurup, 2007;Kumar, Thomy, Deepa, Hashim, & Sudhakar, 2016;Sreedhar, Sudhakar, & Meenakumari, 2013;Venu & Kurup, 2002, 2006. Estimation of LWR equations are very important in the fishery assessment where they are used to predict the weight-at-age from the length-in-yield assessments (Garcia et al, 1998;Pauly, 1993), calculating the condition indices (Anderson & Gutreuter, 1983), and for morphological comparison of growth rate of different populations (Petrakis & Stergiou, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2013). Difference in the estimations could be regional differences in the growth patterns as confirmed by various authors (Kumar et al, 2016;Sreedhar et al, 2013). Present study could not find any significant difference between the sexual dimorphism in growth pattern are in agreement with the previous findings of Quincoces, Santurtun, & Lucio, 1998. There are many factors affects the LWRs of fishes, such as maturity stages, geographical locality, food supply and physicochemical properties of water etc.…”
Section: Discussionmentioning
confidence: 57%
“…These estimates are also essential for calculating the condition indices and to compare the growth pattern of the fishes between sexes, seasons and region, if a standardized methodology is adopted during the sampling (Froese, 2006;Kumar, Thomy, Hashim, & Sudhakar, 2018;Petrakis & Stergiou, 1995). LWRs of deep-sea fishes are relatively less compared to pelagic fish species (González, Román-Marcote, & Paz, 2009;Kumar et al, 2018;Kumar, Thomy, Deepa, Hashim, & Sudhakar, 2016). It is also noted that limited information is available on the biology, distribution and life history pattern of deep-sea fishes of India, which is quite renowned for their rich deep-sea fishery resources (Hashim, 2012;Sreedhar, Sudhakar, & Meenakumari, 2013;Venu, 2009;Vinu, 2017) especially LWRs (Jayapraksh et al, 2006;Kumar et al, 2016Kumar et al, , 2018Sreedhar et al, 2013;Vinu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation